Effect of Clay Core Configuration of the Rock Fill Dams Against Hydraulic Fracturing. (2017) - Djarwadi, Didiek; Suryolelono, Kabul Basah; Suhendro, Bambang; Hardiyatmo, Hari Christady
Abstract: Hydraulic fracturing occurred in Hyttejuvet dam in Norway during its first impounding. The water containing soil particle was emerging from the downstream toe of the dam. The water level on the reservoir was then lowered in order to reduce the potential of failure. Further investigation indicated that the clay core configuration was the main caused of the hydraulic fracturing to occur. The clay core material was moraine till soils. Due to the pore water pressure dissipation in the core was very slow, the upstream slope was steepened. This practice increased the arching effect and load transfer between embankment zones. This paper studies the effect of clay core configuration on the rock fill dams against hydraulic fracturing using numerical analysis. The configuration of the Hyttejuvet dam was analyzed using finite element method. Couple analyses between stress & deformation and seepage analyses were used. The stress and deformation during construction was then used as initial stress in the couple analysis with increasing water in the reservoir. When the effective vertical stresses in the upstream face of the clay core was less than the water pressure in the reservoir, hydraulic fracturing will occur. In order to investigate the effects of clay core materials in the analyses, the clay core material was replaced by clay core materials used in 5 major dams in Indonesia The variation of the clay materials were made in the 6 different fine contents. There were 30 variations of the clay core materials were analyzed. The results indicated that hydraulic fracturing was still occurred in the relatively same locations, event the clay core materials were replaced by 30 variations. The analyses results indicated that the configuration of clay core of the rock fill dam strongly influence to the hydraulic fracturing.